The Role of the International Res~rve~ in Financing the Private Investment m Libya - الفضلي, أ.عيسى صالح (Dirasat in Economics and Business, 2004)
The Availability of interna-ti onal reserves in a suitable size iscon sidered an important case forth e economic activity in anycountry.Peter Clark argues thatavailability of reserves act as abuffer stock against future crises.It raises the trust in the country's financial management, enabling itto protect its level of consum-ption, production and economicgrowth against temporary and seasonally falls in the price andrevenues of its exports and/orthe unexpected rise in imports prices. In addition to that, ithelps supporting the stability ofexchange rate policy .